2020
DOI: 10.2147/ppa.s243734
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Medication Adherence for Pulmonary Tuberculosis Patients During Continuation Phase in Dalian, Northeast China</p>

Abstract: Purpose: Medication adherence is crucial for decreasing the burden of tuberculosis, but few relevant studies have been conducted in northeast China. This study aimed to explore the level of medication adherence among pulmonary tuberculosis outpatients and the predictive factors based on the bio-psycho-social medical model. Patients and Methods: A cross-sectional multi-center survey was conducted in four tuberculosis medical institutions in Dalian, northeast China. Medication adherence was measured using the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
3
24
0
7
Order By: Relevance
“…In general, adherence to treatment in CAD ranges from 40%-60%. 13 This measure has been reported to be 59% in Iran. 14 On the other hand, chronic diseases can be weakly managed in developing countries due to shortage of health resource.…”
Section: Introductionmentioning
confidence: 99%
“…In general, adherence to treatment in CAD ranges from 40%-60%. 13 This measure has been reported to be 59% in Iran. 14 On the other hand, chronic diseases can be weakly managed in developing countries due to shortage of health resource.…”
Section: Introductionmentioning
confidence: 99%
“…Study design and setting. This multi-centre survey was conducted between June 20, 2019, and August 31, 2019, and four medical institutions in Dalian, Liaoning Province, in northeast China were involved 41 . The four TB medical institutions, which served different types of patients, were chosen according to their institution level and location.…”
Section: Methodsmentioning
confidence: 99%
“…A parent or legal guardian provided informed consent for any patient under the age of 18. Detail description can be found in our another study 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported on factors that influence adherence to TB treatment, including age, employment, and lifestyle choices, such as consuming alcohol [46], [47]. Other intrinsic factors that influence treatment adherence are knowledge about TB [47], [48], [49], including drug side effects and having a positive self-image and self-awareness [50]. In contrast to adherence, a factor that influences nonadherence to TB treatment is the side effects of the medication.…”
Section: Antecedentsmentioning
confidence: 99%